Harvest in the native Slavic names of months - Bońkowski, Robert (Papers in Linguistics, 2024)
The article examines the official native Slavic month names motivated by harvest, i.e. historically the most important moment during the summer season. The importance of harvest is evidenced by the range of terms referring to all the activities farmers had to perform, such as reaping, threshing and cleaning the cut grain. In addition, these names also refer to the tool used to cut the ears of grain. Alongside the enumerated terms, one also encounters references to the name of one species of cut grain, as well as to the transportation of harvested grain to farm buildings. Analysed etymologically, but also culturally, these names prove to be among the elements shaping the national identity of individual Slavic peoples and to reflect the linguistic image of the world as seen from the perspective of summer fieldwork. As such, they also undeniably represent cultural heritage.